Organic carbon and the generation of organic matter in bays of the White Sea. - Maksimova, M P; Vladimirskiy, S S (PANGAEA, 1990)
Analysis of contribution of micronodules of sand and silt size to chemical composition of various types of pelagic sediments, as well as use of published data indicate that in some types of bottom sediments micronodules are the principal carriers of manganese and nickel. These elements appear to constitute smaller fractions of colloidal iron and manganese hydroxides, as well as terrigenous material.
(Table 1) Concentrations of organic carbon in bays of the White Sea
Keywords: Archive of Ocean Data; ARCOD; Carbon, organic, total; DEPTH, water; MULT; MV-CB-1; MV-CB-2; MV-CB-3; MV-CB-4; MV-KeB-1; MV-KeB-2; MV-KoB-1; MV-KoB-2; MV-KoB-3; MV-PB-1; MV-PB-2; MV-SoB-1; MV-SoB-2; MV-SuB-1; MV-SuB-2; MV-SuB-3; MV-VSB-1; MV-VSB-2; MV-VSB-3; MV-VSB-4; MV-VSB-5; Organic carbon analyzer, Photochem E3600; White Sea, Chupa Bay; White Sea, Kem Bay; White Sea, Kolezhma Bay; White Sea, Pongoma Bay; White Sea, Soroka Bay; White Sea, Suma Bay; White Sea, Velikaya Salma Bay